THE INTERACTION OF ORTHOPHOSPHORIC ACID AND FLY-ASH - ARSLAN, M; BOYBAY, M (Elsevier Science Bv, 1993)
Coal combustion fly ash is produced as a byproduct of the burning of pulverized coal. An investigation has been conducted to study the interaction of fly ash and orthophosphoric acid. The work was carried out with two typical fly ashes both in solid phase and in the phosphoric acid solution. The effects of acid concentration, contact time, pH, temperature, solid/liquid ratio and particle size distribution upon the interaction, P2O5 distribution and reaction products were examined. The oxides of aluminum, iron, calcium and magnesium as the principal constituents of fly ash were reacted with phosphoric acid to produce crystalline and amorphous phosphates. The precipitated reaction products were Ca(H2PO4)2.H2O, K,...(Al,Fe)3H14(PO4)8.4H2O, beta-Ca2P2O7 and (Ca,Mg)3(PO4)2 (at high temperature). The interaction begins between the outer shell of fly ash particles and phosphoric acid. The chemical reaction proceeds with the diffusion of acid into the particles.
Keywords: FLY ASH; CHARACTERIZATION; UTILIZATION; ORTHOPHOSPHORIC ACID